Continuing conversations: Moving support for doctoral supervisors' professional development online. Issue 6 (2nd November 2021) - Vaughan, Sian; Blackburn, Carolyn; Curzon, Rachel
ABSTRACT: Whilst doctoral supervision online has become almost routine, the COVID19 pandemic significantly changed research supervision. Supervisors were distanced from colleagues and co-supervisors, with less opportunity for the informal and unplanned conversations through which supervisory challenges may be shared and mentoring take place. An accredited Communities of Practice for Doctoral Supervision has been in operation at Birmingham City University since 2015. Designed to run face to face with small groups, the programme moved online in Spring 2020 due to the lock-down in the UK. Surveying the experiences of facilitators and participants, this paper reflects on the challenges and changes of moving conversations online. Online professional development did require more structured facilitation to effectively support openness, honesty and trust amongst supervisors. Whilst online tools bring benefits in accessibility and democracy, a fundamental component of the successful move online was identified as the human element, supervisors as facilitators crafting a sense of community and belonging.